Progress in the cryoablation and cryoimmunotherapy for tumor - Chen, Zenan; Meng, Liangliang; Zhang, Jing; Zhang, Xiao (Frontiers in Immunology, 2023)
With the rapid development of imaging equipment and minimally invasive technology, cryoablation technology is increasingly used in minimally invasive treatment of tumors, mainly for patients with advanced tumors who cannot be surgically resected or cannot tolerate surgery, and patients with early tumors who voluntarily accept ablation. Compared with other thermal ablation techniques such as radiofrequency and microwave, cryoablation is more efficient and safer for target lesions. In addition, in the study also found that cryoablation, not only can cause tumor tissue necrosis and apoptosis, but also can promote the release of tumor-derived autoantigens into the circulation, stimulate the host immune system to produce favorable anti-tumor immune effects against primary and result in regression of the primary tumor and distant metastasis, the additional effect called " Accompanying effects ". It is the basis of combined ablation and immunotherapy for tumor. At present, there are many researches on the mechanism of immune response induced by cryoablation and how to positively induce immune response. In this review, we focus on the immune effects induced by cryoablation, the effect and mechanism of tumor immunotherapy combined with cryoablation in the treatment of tumors, and the clinical research of this combination therapy.